Self-diffusion in high-purity α-Al2O3: Comparison of Ti-doped, Mg-doped and undoped single crystals. Issue 1 (January 2021) - Fielitz, Peter; Ganschow, Steffen; Kelm, Klemens; Borchardt, Günter
Abstract: Oxygen diffusivity in α-alumina is characterised by a scatter band of about one decade and a half in an Arrhenius diagram. In order to control decisive material parameters the present study is based on high-purity single crystals which were deliberately doped with aliovalent elements (Mg or Ti) and simultaneously annealed in an 18 O2 atmosphere (200 mbar at 1650 °C). In such a crucial experiment the diffusivities in undoped and acceptor or donor doped alumina are identical within a factor of about 2. Contradictory findings in the past on the impact of Mg and Ti on the oxygen diffusion can be rationalised due to published similar calculated energies for the most probable dopant incorporation reactions. Al self-diffusion is much more rapid than oxygen diffusion in undoped and Ti-doped α-alumina. In this work we show for the first time that Mg doping drastically reduces the Al diffusivity in α-alumina.